The Use Of Experiential Meanings in the Drink Labels - Dias Andris Susanto (ETERNAL (English Teaching Journal), 2018)
This research is aimed at describing the English sentences used on the experiential meaning in the drink labels. Butt, et al. (1996:44) introducing us to the notion that language simultaneously performs three functions (experiential, interpersonal and textual) and one of the functions which is focused on the process is that experiential meanings. The objectives of this research are to investigate clauses and their constituents realized in the English sentences on the drink labels and to map out the experiential meanings realized in the clauses in the drink labels. The writer used qualitative descriptive analysis to find out the characteristics of English sentences used in the drink labels. The object of the study is the sentences used in the drink labels. The unit analysis is a clause used in the drink labels. The data were collected by the use of documents. To analyze the data, Method of data analysis, the writer took some steps; there are identification of 19 products of the drink labels, identification of the labels, identification of the sentences used in the drink labels, and identification of the experiential meaning. The result shows that, the 19 drink labels have 79 clauses and each clause has different constituents there are two, three, four, five, six, seven, eight, nine, and ten constituents. The dominant constituent is nine constituents. Discussion on Experiential meaning, there are participant, process, and circumstance. The dominant process is material process. It has 50 clauses. Then the relational process is lees dominant, it has 29 clauses. In addition, the last process is projecting. It has no clauses. It is suggested that labels are good media for teaching English, especially systemic functional linguistics. By understanding the meaning of the labels, students and or readers are able to get the knowledge about the meanings of the clauses in the drink labels. They also can get the benefit of consuming the drinks. The other researchers would be able to continue analyzing for the next steps using different point of views.